2007
DOI: 10.1016/j.bmc.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The use of aminoglycoside derivatives to study the mechanism of aminoglycoside 6′-N-acetyltransferase and the role of 6′-NH2 in antibacterial activity

Abstract: Aminoglycoside antibiotics act by binding to 16S rRNA. Resistance to these antibiotics occurs via drug modifications by enzymes such as aminoglycoside 6′-N-acetyltransferases (AAC(6′)s). We report here the regioselective and efficient synthesis of N-6′-acylated aminoglycosides and their use as probes to study AAC(6′)-Ii and aminoglycoside-RNA complexes. Our results emphasize the central role of N-6′ nucleophilicity for transformation by AAC(6′)-Ii and the importance of hydrogen bonding between 6′-NH 2 and 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…3B) were designed to display an N-6 0 substituent containing a hydrogen bond donor for interaction with A1408, and attachment of this group via an amide bond was expected to prevent acetylation by AAC(6 0 ). 84 As expected, compounds 2a and 2b were not substrates of AAC(6 0 )-Ii. However, bacterial studies with E. coli Fig.…”
Section: Aminoglycoside N-6 0 Derivativessupporting
confidence: 65%
See 1 more Smart Citation
“…3B) were designed to display an N-6 0 substituent containing a hydrogen bond donor for interaction with A1408, and attachment of this group via an amide bond was expected to prevent acetylation by AAC(6 0 ). 84 As expected, compounds 2a and 2b were not substrates of AAC(6 0 )-Ii. However, bacterial studies with E. coli Fig.…”
Section: Aminoglycoside N-6 0 Derivativessupporting
confidence: 65%
“…70,[78][79][80][81][82][83] To address this issue, compounds 2a-b ( Figure 3B) were designed to display an N-6′ substituent containing a hydrogen bond donor for interaction with A1408, and attachment of this group via an amide bond was expected to prevent acetylation by AAC(6′). 84 As expected, compounds 2a-b were not substrates of AAC(6′)-Ii. However, bacterial studies with E. coli revealed that antibacterial activity was also compromised to some extent compared to neamine.…”
Section: Aminoglycoside N-6′ Derivativesmentioning
confidence: 91%
“…[107][108][109][110][111] Nanomolar bisubstrate inhibitors where an AG is conjugated to coenzyme A (CoA) were reported. 112,113 Structure-activity relationship (SAR) studies of truncated CoA bisubstrate revealed that the pantetheinyl group is not necessary for recognition by the enzyme, but at least one phosphate group is needed. 114 Following up with amide-linked analogues, various sulfonamide-, sulfoxide-, and sulfonecontaining bisubstrate inhibitors were synthesized and found to be 40-fold less potent against AACIJ6′)-Ii when compared to their amide-linked counterparts.…”
Section: Patent Us 849354 B2 (Ref 82)mentioning
confidence: 99%
“…Auclair and co‐workers have reported amide, phosphonate, and sulfonamide‐linked aminoglycoside–CoA bisubstrates to probe AAC(6′) enzymes (Figure 19). 157159 Additionally, 6′‐N‐acylated aminoglycosides have been applied as probes to study AAC(6′) and aminoglycoside–RNA complexes 160. These studies have provided insight into the mechanistic details of resistance enzymes like AACs and structural features of aminoglycosides that dictate how bacteria avoid the action of aminoglycosides.…”
Section: New Tools and Recent Developments For Aminoglycosides' Inmentioning
confidence: 99%